Pengaruh Smart Quiz Game Terhadap Pengetahuan dan Sikap Siswa Tentang PHBS Pada Tatanan Sekolah di SMPN 5 Kota Bengkulu - Ican Hidayat; Lissa Ervina; Efrizon Hariadi (Poltekkes Kemenkes Jambi, 2025)
Background: The implementation of PHBS in the school environment is crucial because school-age children are in a critical phase and vulnerable to various health problems. Campaigns to encourage the implementation of PHBS are a preventative measure that can be implemented through schools to help students maintain and improve their health, prevent disease, and reduce risky behaviors. The purpose of this study was to determine the effect of the smart quiz game on students’ knowledge and attitudes about PHBS in the school setting. Method: The population in the studyiusediaisimpleirandomisampling technique with a sample of 33 people. The instrument tool was a questionnaire. Knowledge dataianalysis with theiWilcoxonisignedirankitest. I Results: The results of the statistical test analysis to see the average knowledge of respondents with the results before the intervention (55.45) after (89.39) the difference in mean rank (33.94), obtained p = 0.000 meaning there is an influence of smart quiz games on knowledge about PHBS Schools at SMPN 5 Bengkulu City. The results of the statistical test of the average attitude of respondents with before the intervention (32.82) after (38.70) the difference in mean rank (5.88), the results of the Wilcoxon test obtained p = 0.000 meaning there is an influence of smart quiz games on attitudes about PHBS Schools at SMPN 5 Bengkulu City. Conclusion: there was an influence of the smart quiz game on knowledge and attitudes about PHBS Schools at SMPN 5 Bengkulu City